A sensor to monitor limb depth in transtibial sockets with locking pin suspension: a technical note. Issue 4 (19th August 2021) - Bennett, Sam; Gurrey, Clement; Wang, Horace; Weissinger, Mathew; Larsen, Brian; Sanders, Joan E.
Abstract : Background: Monitoring of limb depth in transtibial sockets may provide useful information toward patient education and care. Objective: The objective was to develop a sensor to detect the depth of a locking pin in the shuttle lock of a transtibial socket and to monitor the small motions between ratchet clicks during ambulation. Study design: Controlled bench testing and single-participant study. Methods: A copper wire coil positioned beneath the socket shuttle lock was used with an inductive sensing chip to monitor locking pin depth. A custom jig was used to calibrate the sensor and bench test the system. Repeatability, drift, and the effects of pin length, carbon fiber presence, temperature change, and pin angulation on sensor performance were tested. Testing was conducted on a participant wearing an adjustable socket, walking with the panels at four different radial positions. Results: The sensor demonstrated a root mean square error of 0.21% of the full-scale output. Different pins, different pin lengths, and the presence of carbon fiber affected calibration, indicating that the sensor must be calibrated to the individual user's socket and pin. Ratchet clicks and cyclic motion between clicks during walking were evident in the data. During participant testing, enlarging the socket at 1.00 mm radial increments caused significant changes in pin peak-to-peak distance (up and down motion) within a step. Conclusions: The sensor is sufficiently accurate to pursue studies investigating utility of the data toward clinical monitoring of socket fit.